Identification and Evaluation of the Urinary Microbiota Associated With Bladder Cancer - Nannan Li; Lei Wang; Qin Yang; Fuqiang Li; Zhun Shi; Xiujie Feng; Liwei Zhang; Xiaojian Li; Xin Jin; Shida Zhu; Kui Wu; Ningchen Li (Cancer Innovation)
ABSTRACT Background Bladder cancer is a common malignancy of the genitourinary system. Recent studies have confirmed the existence of microorganisms in urine. This study aimed to characterize changes in the urinary microbiota of Chinese bladder cancer patients and determine differences between patients with muscle‐invasive bladder cancer (MIBC) and those with non‐muscle‐invasive bladder cancer (NMIBC). Methods Urine samples were collected from 64 patients with bladder cancer and 94 disease‐free controls using the clean catch method and sequenced by 16S rRNA gene sequencing. Sequencing reads were filtered by VSEARCH and clustered by UPARSE. Results Significant associations were found between urinary microbiota and factors such as sex, age, and disease status. After age adjustment, differences in beta diversity were observed between healthy men and women, cancer patients and healthy controls, and NMIBC and MIBC patients. The cancer patients had an increased abundance of 14 bacterial genera, including Stenotrophomonas, Propionibacterium, and Acinetobacter. Notably, Peptoniphilus spp. were enriched in high‐risk MIBC patients, indicating their potential as a risk marker. Functional prediction via PICRUSt analysis suggested enriched metabolic pathways in specific disease groups. Furthermore, molecular ecological network analysis revealed differences based on sex and disease type. Conclusions This significant microbial diversity indicates a potential correlation between urinary microbiota dysbiosis and bladder cancer, with implications for risk stratification and disease management. The identified urinary microbiota may serve as noninvasive markers for bladder cancer, warranting further validation in larger cohorts. This study provides a foundation for further research on the mechanisms of bladder cancer progression.